2020
DOI: 10.1136/bmj.m2412
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of total, animal, and plant proteins and risk of all cause, cardiovascular, and cancer mortality: systematic review and dose-response meta-analysis of prospective cohort studies

Abstract: ObjectiveTo examine and quantify the potential dose-response relation between intake of total, animal, and plant protein and the risk of mortality from all causes, cardiovascular disease, and cancer.DesignSystematic review and meta-analysis of prospective cohort studies.Data sourcesPubMed, Scopus, and ISI Web of Science until December 2019, and references of retrieved relevant articles.Study selectionProspective cohort studies that reported the risk estimates for all cause, cardiovascular, and cancer mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 86 publications
(516 reference statements)
5
154
1
9
Order By: Relevance
“…High protein intake during pregnancy has been reported to increase the risk of small-for-gestational-age infants 32 and neonatal death. 33 While inconsistent results regarding renal function 34 and cancer mortality 35 have been reported, some studies report that high protein intake is associated with lower renal function in individuals with mild renal insufficiency 36 and that high consumption of animal proteins is associated with a higher risk of cancer mortality in middle-aged individuals. 37 Thus, consuming moderate amounts of protein to maintain overall nitrogen balance is important in these populations, particularly because of the risks associated with excessive protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…High protein intake during pregnancy has been reported to increase the risk of small-for-gestational-age infants 32 and neonatal death. 33 While inconsistent results regarding renal function 34 and cancer mortality 35 have been reported, some studies report that high protein intake is associated with lower renal function in individuals with mild renal insufficiency 36 and that high consumption of animal proteins is associated with a higher risk of cancer mortality in middle-aged individuals. 37 Thus, consuming moderate amounts of protein to maintain overall nitrogen balance is important in these populations, particularly because of the risks associated with excessive protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in cancer risk may be associated with increased folate-cycle driven metabolism, such as increasing nucleotide synthesis, to the benefit of rapidly dividing cancer cells. One could hypothesize a similar effect for methionine, but a recent meta-analysis comparing high plant protein intake to high animal protein intake found no change in cancer-associated mortality, though there was an increase in all-cause mortality with a high animal protein diet [147].…”
Section: High Serum B9/b12 Levels and Cancermentioning
confidence: 99%
“…However, there are still significant gaps at both the population and individual level concerning dietary guidelines to maintain health. Several reviews and investigations have focused on defining appropriate nutrient intakes for improved BC patient outcomes (100,166,(184)(185)(186)). Yet, changes in life-style and food choices represent a challenge for BC patients; for example, Shi et al found that newly diagnosed with BC consistently consume excessive fat and slightly increased consumption of fruits and vegetables following diagnosis (166).…”
Section: Discussion On Challenges and Gaps For Nutritionally Relevantmentioning
confidence: 99%